Supporting Nutritional Status and Physical Activity in Patients with Chronic Obstructive Pulmonary Disease: A Feasibility Study of a Complex Intervention - Tanja Sofie Hansen; Pia Søe Jensen; Vibeke Nørholm; Mia Ingerslev Loft; Ingrid Poulsen (COPD)
Objective To assess the feasibility and acceptability of a nurse-led COllective PErson-centred dialogue (COPE-Dialogue) intervention developed though co-production focusing on nutritional and physical activity support to hospitalised patients with Chronic obstructive pulmonary disease.Methods A non-randomised feasibility study according to the Medical Research Council framework for developing and testing a complex intervention. The intervention consisted of a dialogue tool with three components related to nutrition and physical activity: (1) A needs assessment, (2) Recommendations for support (3) Transitional information. Data from patients and nurses was collected from January through March 2024. Recruitment, fidelity, and acceptability were measured with qualitative and quantitative approaches including progression criteria. Qualitative content analysis and descriptive statistic were applied in the analysis.Results Recruitment was feasible, with 77% patients participating. Fidelity was high for the needs assessment and recommendations. Transitional information needs modification and should be combined with a relational contact. Patients and nurses found the dialogue tool acceptable and meaningful but faced time constraints.Conclusions The dialogue tool was feasible regarding recruitment and fidelity. The tool was acceptable and meaningful to both patients and nurses, while modification is required in the transitional information. However, there is a need to strengthen the quality of the fundamental care within nutritional and physical activity combined with clinical management support.